2013
DOI: 10.3892/mmr.2013.1446
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil suppresses bone resorption by inhibiting osteoclastogenesis through decreased expression of M-CSF, PU.1, MITF and RANK in ovariectomized rats

Abstract: Previous studies have identified a positive correlation between the intake of n‑3 fatty acids and bone mineral density in postmenopausal women. The aim of the present study was to determine the effects of fish oil on bone metabolism and to investigate the underlying mechanism using ovariectomized rats. Ovariectomized or sham‑operated (sham) female rats were fed AIN‑76A‑based diets containing 5% corn or fish oil for 2 weeks. Fish oil was found to decrease the plasma levels of arachidonic and linoleic acids, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…However, long-term estrogen replacement therapy can increase the risk of endometrial and breast cancers. Therefore, many investigators have focused their efforts on developing a new anti-resorptive agent that does not have side effects [7][10]. Because osteoclasts function in bone resorption, specifically inhibiting osteoclasts has been considered the main target in numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term estrogen replacement therapy can increase the risk of endometrial and breast cancers. Therefore, many investigators have focused their efforts on developing a new anti-resorptive agent that does not have side effects [7][10]. Because osteoclasts function in bone resorption, specifically inhibiting osteoclasts has been considered the main target in numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no significant effect of n-3 PUFA on the bone expression of RANKL or its decoy receptor OPG, which are also important determinants of osteoclastic differentiation and activation (5) . Previous in vitro and in vivo studies examining the effects of n-3 PUFA on the RANKL/OPG pathway reported mixed results (32)(33)(34) . Sacco et al (35) reported that shortterm (2 weeks) periods of n-3 PUFA (flaxseed oil) supplementation resulted in no changes in the serum level of RANKL or in the OPG:RANKL ratio in OVX rats, but that E 2 treatment did result in such changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism is still not completely understood. MITF and its co-activator PU.1 have recently been designated as a reliable target responsible for osteoclastogenic disorders [13]. It is known that osteoclasts shared a common origin with preadipocytes, but they were mutually exclusive with each other in the differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…There was tight synergy in the transcription of those genes and/or modulation of their downstream genes. For these reasons, MITF and PU.1 are regarded as a target for treatment of osteopathic conditions, such as bone resorption and osteopetrosis [13]. …”
Section: Introductionmentioning
confidence: 99%